Moral Values behind the Reliefs’ Story of The Sojiwan Temple at Klaten Region - Shadikah, Arina Afiyati (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2022)
This research was conducted at Sojiwan Temple, Klaten. The Sojiwan Temple is a Buddhist Temple located in Klaten Region. This research aimed to investigate the Reliefs’ shapes that existed at Sojiwan Temple and the story of Temples’ Reliefs. There were some related researches to the previous study. However, the gap was found. It is about the moral values based on story behind the Temple’s Reliefs at the Sojiwan Temple. There was a qualitative research design employed in this study. The object of this research was Sojiwan Temple itself. There were three data collection techniques used to collect the data. They were observation, interview and documentation. The data gathered were analyzed using a research design called flow method of qualitative design. This research method consisted of three stages, those namely collecting data, reducing data, displaying data, and concluding or verifying. The result of this study indicated that: (1) there were fourteen Reliefs’ shapes existed at Sojiwan Temple and (2) Each Relief at Sojiwan Temple had moral values based on its own story sculpted. All the Reliefs told about some moral values. They were ingenuity, simplicity, tolerance, sincerity, discipline, toughness, affection, carefulness, self-awareness, solidarity, and unity. Penelitian ini dilaksanakan di Candi Sojiwan, Klaten. Candi Sojiwan merupakan candi Buddha yang terletak di Kabupaten Klaten. Tujuan dari penelitian ini adalah untuk menemukan bentuk-bentuk Relief yang ada di Candi Sojiwan beserta dengan makna dari masing-masing Relief tersebut. Dalam penelitian-penelitian terdahulu sudah membahas tentang hal serupa. Namun, terdapat perbedaan yang ditemukan yaitu tentang nilai-nilai moral yang diperoleh dari makna dan cerita di balik Relief yang ada di Candi Sojiwan. Penelitian ini menggunakan metode kualitatif. Adapun objek dalam penelitian ini adalah Candi Sojiwan itu sendiri. Terdapat tiga teknik pengumpulan data yang digunakan dalam penelitian ini, yaitu observasi, wawancara, dan dokumentasi. Data yang diperoleh kemudian dianalisis menggunakan desain penelitian yang disebut dengan metode kualitatif flow. Metode penelitian yang digunakan ini memiliki tiga tahap, yaitu mengumpulkan data, mengurang data, menampilkan data, dan menyimpulkan atau memvalidasi. Hasil penelitian ini menunjukkan bahwa: (1) terdapat empat belas bentuk Relief yang ada di Candi Sojiwan dan (2) masing-masing Relief memiliki nilai moral yang terkandung dalam cerita dari masing-masing Relief. Semua Relief tersebut menyampaikan nilai-nilai moral, yaitu kecerdikan, kesederhanaan, toleransi, ketulusan, disiplin, ketabahan, kasih sayang, kehati-hatian, mawas diri, solidaritas, dan persatuan.